Seroprevalence and risk factors of Peste des Petits Ruminants in sheep and goats in Sudan - Salih, Huyam Ahmed MohammedElamin; Elfadil, Abdelhamid Ahmed Mohammed; Saeed, Intisar Kamil; Ali, Yahia Hassan (Journal of Advanced Veterinary and Animal Research, 2014)
The seroprevalence and risk factors of Peste des Petits Ruminants (PPR) were determined in unvaccinated sheep and goats in Sudan. A total of 480 sera samples were collected from the sheep (n=261) and goats (n=219) of Sennar, Gedarif, River Nile, and North Kordofan states during May, June, and October 2012 and February 2013, respectively. The sera were tested for the presence of antibodies against PPR using competitive Enzyme Linked Immunosorbent Assay. The overall seroprevalence of PPR was recorded as 45.6% (n=219/480); whereas, 57.2% in Sennar, 46.2% in Gedarif, 34.9% in River Nile and 39.8% in North Kordofan. A total of 14 risk factors were investigated using structured questionnaire, of which 9 were found to be associated with PPR seroprevalence (p?0.05). Among the localities, Abozabad located in North Kordofan had the highest prevalence (91.7%) of PPR followed by Barbar in River Nile. PPR seroprevalence was higher in pastoralists, animals housed in scarp fences, females, and Kwahla sheep. In addition, PPR was higher in the states that had high rainfall and wind-speed. The associated 9 factors were further analyzed multivariably by logistic regression, and finally 5 of them (states, localities, husbandry system, gender, and age) were found to be associated with PPR seroprevalence (p?0.05). DOI: http://dx.doi.org/10.5455/javar.2014.a12 J. Adv. Vet. Anim. Res., 1(2): 42-49, June 2014